Socio-demographic characteristics and quality of life of elderly patients with systemic arterial hypertension who live in rural areas: the importance of nurses' role Características sociodemográficas y calidad de vida de ancianos con hipertensión arterial sistémica que viven en la zona rural: importancia del papel del enfermero Características sociodemográficas e qualidade de vida de idosos com hipertensão arterial sistêmica que residem na zona rural: importância do papel do enfermeiro - Darlene Mara dos Santos Tavares; Mariana Mapelli de Paiva; Flavia Aparecida Dias; Marina Aleixo Diniz; Nayara Paula Fernandes Martins (Universidade de São Paulo, 2013)
OBJECTIVE: To describe the socio-demographic characteristics and quality of life of elderly patients with systemic arterial hypertension; to correlate the quality of life with the time of diagnosis and number of medication, as well as to compare the quality of life with the type of medication. METHOD: In this cross sectional home survey design, 460 elderly people from rural areas were involved. The data was collected with the use of the following instruments: World Health Organization Quality of Life-bref and World Health Organization Quality of Life Olders. A descriptive analysis, Pearson correlation and t-Student test (p<0.05) were undertaken. RESULTS: Predominant patient characteristics were: women between the age of 60 and 70, married, four to eight years of formal education, income of one minimum wage, living with their partners. The time of diagnosis was associated with lower quality of life in the physical domain. Elderly patients who used Inhibitors and Angiotensin Converting Enzyme and who did not use AT1 blocker had lower scores in relation to functioning of the senses. Those who used calcium channel blocker scored higher in relation to autonomy. CONCLUSION: there is a need for actions to control systemic arterial hypertension and its associated complications, with the purpose of improving quality of life. OBJETIVO: Describir as características sociodemográficas y la calidad de vida de ancianos con hipertensión arterial sistémica; correlacionar la calidad de vida con el tiempo de diagnóstico y con el número de medicamentos y comparar la calidad de vida con el tipo de medicamento. MÉTODO: Se trata de un estudio del tipo encuesta domiciliar, transversal, desarrollado con 460 ancianos de la zona rural. Fueron recolectados datos mediante los instrumentos: World Health Organization Quality of Life-bref y World Health Organization Quality of Life Olders. Fueron aplicados análisis descriptivo, correlación de Pearson y test t-Student (p<0,05). RESULTADOS: Predominó el sexo femenino, 60├ 70 años, casados, 4├ 8 años de estudio, renta de un salario mínimo y vivir con pareja. El tiempo de diagnóstico se asoció a menor calidad de vida en el dominio físico. Los ancianos que utilizaban Inhibidores de la Enzima Convertidora de Angiotensina y no utilizaban bloqueador AT1 mostraron menor score en autonomía. CONCLUSIÓN: son necesarias acciones para controlar la hipertensión arterial sistémica y sus complicaciones, de manera a favorecer la calidad de vida. OBJETIVO: descrever as características sociodemográficas e a qualidade de vida dos idosos com hipertensão arterial sistêmica, correlacionar a qualidade de vida com o tempo de diagnóstico e com o número de medicamentos e comparar a qualidade de vida com tipo de medicamento. MÉTODO: trata-se de estudo do tipo inquérito domiciliar, transversal, realizado com 460 idosos da zona rural. Coletaram-se os dados por meio dos instrumentos: World Health Organization Quality of Life-bref e World Health Organization Quality of Life Olders. Realizaram-se análise descritiva, correlação de Pearson e teste t de Student (p<0,05). RESULTADOS: predominaram: sexo feminino, 60├70 anos, casados, 4├ 8 anos de estudo, renda de um salário-mínimo e morar com cônjuge. O tempo de diagnóstico associou-se à menor qualidade de vida no domínio físico. Os idosos que utilizavam inibidores da enzima conversora de angiotensina e não utilizavam bloqueador AT1 apresentaram menor escore no funcionamento dos sentidos. Os que utilizavam bloqueador do canal de cálcio apresentaram maior escore na autonomia. CONCLUSÃO: são necessárias ações para controle da hipertensão arterial sistêmica e suas complicações, de forma a favorecer a qualidade de vida.